Analisis Rantai Markov untuk Mengetahui Peluang Perpindahan Konsumen Dalam Pemilihan Platform Online Food Delivery: Penelitian - Alvi Sahrin Nasution; Sri Masnito Pardosi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study examines consumer switching behavior across online food delivery platforms using the Markov chain method. Food delivery services such as GrabFood, GoFood, and ShopeeFood have gained increasing popularity, particularly among university students, due to their convenience, speed, and diverse promotional offers. However, intense competition among these providers has led to a growing trend of consumers shifting from one platform to another. The research involved students from the Mathematics Study Program, class PSM 22 B, Universitas Negeri Medan, as respondents. Data were collected through questionnaires and analyzed to construct a transition probability matrix that represents the likelihood of consumers switching platforms. The results indicate that the steady-state condition is reached in the eighth period, with a stable market distribution consisting of 22% for GrabFood, 48% for GoFood, and 30% for ShopeeFood. These findings demonstrate that the Markov chain provides a quantitative representation of long-term consumer switching patterns. Furthermore, the study emphasizes that understanding such switching behavior can serve as a crucial foundation for service providers to design effective marketing strategies, enhance customer loyalty, and maintain market share in an increasingly competitive industry.